Role of steric crowding of ligands in the formation of hydroxido bridged di- and trinuclear copper(II) complexes: Structures and magnetic properties. (1st May 2018) - Bhowmik, Pallab; Jana, Subrata; Mahapatra, Prithwish; Giri, Sanjib; Chattopadhyay, Shouvik; Ghosh, Ashutosh
Graphical abstract: Three new hydroxide bridged Cu(II) complexes have been synthesized using three tridentate NNO donor Schiff bases and characterized by single-crystal X-ray diffraction. Two of the complexes consist of a trinuclear core, whereas other one is a dinuclear complex. Variable temperature magnetic susceptibilities measurements show antiferomagnetic coupling between the Cu(II) centres. Abstract: Two new trinuclear copper(II) complexes, [(CuL 1 )3 (μ3 -OH)](ClO4 )2 (1 ) and [(CuL 2 )3 (μ3 -OH)](ClO4 )2 ·5H2 O (2 ), and one new dinuclear Cu(II) complex, [(CuL 3 )2 (μ2 -OH)(CH3 OH)]ClO4 (3 ), have been synthesized using three tridentate NNO donor Schiff bases, HL 1, HL 2 and HL 3 (HL 1 = 1-((2-aminoethylimino)methyl)naphthalen-2-ol, HL 2 = 1-((2-(methylamino)ethylimino)methyl)naphthalen-2-ol and HL 3 = 1-((2-(dimethylamino)ethylimino)methyl)naphthalen-2-ol), respectively and structurally characterized by single-crystal X-ray diffraction. Complexes 1 and 2 consist of trinuclear [(CuL)3 (μ3 -OH)] 2+ units, whereas 3 contains dinuclear [(CuL)2 (μ2 -OH)] + unit along, with perchlorate anions which are needed to balance the charge. In each of the complexes, all the copper atoms are five-coordinated with a distorted square-pyramidal geometry, except for complex 1 in which one of the Cu(II) ions of the trinuclear unit is six-coordinate, being weakly coordinated to one of the perchlorate anions to form an elongated distorted octahedron. The equatorial plane consists of the bridging oxygen of the central OH − group together with three atoms (NNO) from the Schiff base. The phenoxido oxygen atom of the Schiff base coordinates to the axial position of the Cu(II) ion of another subunit to form the cyclic trimer in 1 and 2 and dimer in 3 . Magnetic measurements of complexes 1 –3 in the 2–300 K temperature range indicate antiferromagnetic coupling in the complexes with J = −8.85, −4.86 and −50.60 cm −1 for 1 –3 respectively. Density Functional Theory has also been performed in order to estimate the exchange coupling constants in these three complexes. The theoretically calculated J values are in good agreement with the experimental values.